2001
DOI: 10.1002/1521-3803(20011001)45:5<317::aid-food317>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Volatile flavour components of baked potato flesh. A comparison of eleven potato cultivars

Abstract: Tubers of eleven cultivars of potato were baked and the flavour compounds from the flesh were isolated by headspace adsorption onto Tenax and analysed by gas chromatography-mass spectrometry (GC-MS). Lipid degradation and the Maillard reaction were the main sources of flavour compounds, accounting for 22-69% and 28-77%, respectively, of the total yields. Various sulfur compounds, methoxypyrazines and terpenes were also identified at lower levels. Relative aroma impact values (RAVs) were calculated by dividing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
6
29
1
1
Order By: Relevance
“…Similar sulfide volatiles have also been identified in onion and turnip (Boelens, de Valois, & van der Gen, 1971;Kallio & Salorinne, 1990;Taveira et al, 2009). Duckham, Dodson, Bakker, and Ames (2001) reported the OTV's of dimethyl trisulfide to be equal to 0.01 ppb and dimethyl disulfide to be 0.2 ppb in baked potatoes. In another study, Boelens et al (1971) determined the OTV of dipropyl disulfide in onions to be 3.2 μg/l in water.…”
Section: Volatile Analysismentioning
confidence: 54%
See 1 more Smart Citation
“…Similar sulfide volatiles have also been identified in onion and turnip (Boelens, de Valois, & van der Gen, 1971;Kallio & Salorinne, 1990;Taveira et al, 2009). Duckham, Dodson, Bakker, and Ames (2001) reported the OTV's of dimethyl trisulfide to be equal to 0.01 ppb and dimethyl disulfide to be 0.2 ppb in baked potatoes. In another study, Boelens et al (1971) determined the OTV of dipropyl disulfide in onions to be 3.2 μg/l in water.…”
Section: Volatile Analysismentioning
confidence: 54%
“…Hexanal has previously been identified by several authors in ingredients such as dehydrated carrot (Soria et al, 2008), turnip (Taveira et al, 2009), celery (MacLeod et al, 1988, butter (Povola & Contarini, 2003), vegetable oil (Stashenko, Ferreira, Sequeda, Martínez, & Wong, 1997) and potato (Longbardi, Casiello, Sacco, Tedone, & Sacco, 2011;Petersen, Poll, & Larsen, 1998). In a study on baked potatoes Duckham et al (2001) reported the OTV of hexanal as 4.5 ppb. Kalua et al (2007) conducted a review of olive oil volatile compounds and reported previously determined OTV's ranging from 75-300 μg/kg in oil.…”
Section: Volatile Analysismentioning
confidence: 94%
“…Cultivar differences in both the composition of flavour compounds (Jensen et al 1999) and in the perceived aroma of boiled tubers (Ulrich et al 2000) have been reported. Levels of flavour compounds of baked tuber flesh are also reported to vary among cultivars (Oruna-Concha et al 2001;Duckham et al 2001). The fatty acids, sugars and amino acids in the raw tubers are precursors of most of the compounds responsible for the flavour that forms when potato tubers are baked (Whitfield and Last 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Изолейцин, лейцин, тирозин и фенилаланин -важные предшественники ароматических соединений, определяющих вкус вареного картофеля (Duckham et al, 2001;Martin, Ames, 2001). Именно изолейцин, лейцин и тирозин являются основными субстратами для реакций Стрекера, в результате которых выделяются летучие альдегиды (метилбутаналь и бензальдегид), которые при дают «миндальный» и «поджаренный/сладкий» аромат вареному картофелю.…”
Section: метаболомика и фенотип картофеляunclassified